The Influence of Skills, Experience and Gender on Audit Decisions (Empirical Study of Mr RI Representatives in Jambi) - Azizah Kholiq; Haryadi; Rita Friyani (Indonesian Journal of Business Analytics, 2024)
This study aims to determine the impact of experience, expertise, and gender on audit judgment (an empirical investigation conducted at BPK RI representatives in Jambi). The study's population consisted of BPK RI Representatives from Jambi Province. The study's sample was a saturated sample, which is a sampling strategy that uses the entire population as a research sample, with 67 respondents and a questionnaire return rate of 61. This study technique makes use of quantitative methods. This study uses primary data from questionnaires given to respondents. The results of the study show that competence has a big influence on audit judgment. This indicates that an auditor's level of knowledge will improve audit judgment and that experience has a significant impact on audit judgment. This proves that the variable of gender has no appreciable effect on the audit judgment; the audit judgment increases with the auditor's experience. audit judgment